Enhanced Strength and Sprint Levels, and Changes in Blood Parameters during a Complete Athletics Season in 800 m High-Level Athletes - Bachero-Mena, Beatriz; Pareja-Blanco, Fernando; González-Badillo, Juan J. (Frontiers in Physiology, 2017)
The purpose of this study was to analyze changes in sprint, strength, hematological, and hormonal parameters in high-level 800 m athletes during a complete athletics season. Thirteen male athletes of national and international level in 800 m (personal best ranging from 1:43 to 1:58 min:ss) participated in this study. A total of 5 tests were conducted during a complete athletics season. Athletes performed sprint tests (20 m and 200 m), countermovement jump (CMJ), jump squat (JS), and full squat (SQ) tests. Blood samples (red and white blood profile) and hormones were collected in test 1 (T1), test 3 (T3) and test 5 (T5). A general increase in the performance of the strength and sprint parameters analyzed (CMJ, JS, SQ, 20 m, and 200 m) during the season was observed, with a significant time effect in CMJ (P < 0.01), SQ (P < 0.01), and 200 m (P < 0.05). This improvement was accompanied by a significant enhancement of the 800 m performance from T3 to T5 (P < 0.01). Significant changes in some hematological variables: hematocrit (Hct) (P < 0.01), mean corpuscular volume (MCV) (P < 0.001), mean corpuscular hemoglobin content (MCHC) (P < 0.001), white blood cells count (WBC) (P < 0.05), neutrophils (P < 0.05), monocytes (P < 0.05), and mean platelet volume (MPV) (P < 0.05) were observed throughout the season. The hormonal response and creatin kinase (CK) did not show significant variations during the season, except for insulin-like growth factor I (IGF-1) (P < 0.05). In conclusion, our results suggest the importance of strength levels in middle-distance athletes. On the other hand, variations in some hematological parameters and a depression of the immune system occurred during the season. Therefore, monitoring of the mechanical, hematological and hormonal response in athletes may help coaches and athletes to optimize the regulation of training contents and may be useful to diagnose states of overreaching or overtraining in athletes throughout the season.